Association between tuberculosis and cocaine on negative outcomes of tuberculosis treatment: a systematic review and metaanalysis - Carpio, Franco (2024)
Tuberculosis (TB) remains a significant global health burden, with substance abuse being a common comorbidity. Cocaine-derived drugs, particularly crack and cocaine hydrochloride, have been associated with poor TB treatment outcomes. Objective: This systematic review aimed to synthesize the evidence on the relationship between crack or cocaine hydrochloride use and TB treatment outcomes. Materials and methods: A comprehensive search was conducted across multiple databases (PubMed, Ovid, EBSCOhost, Lilacs, and Google Scholar) using structured search terms. Eligible studies were included in a meta-analysis performed using STATA 16. Results: Five studies were included in the analysis. Overall, crack or cocaine use was associated with a higher risk of loss to follow-up or non-completion of TB treatment (OR = 2.73; 95% CI: 1.33-5.61). In the subgroup of individuals with active TB, this association was particularly strong for loss to follow-up (OR = 7.029; 95% CI: 2.66-18.57). However, no significant association was observed between crack or cocaine use and treatment non-completion in the latent TB subgroup (OR = 1.26; 95% CI: 0.77-2.05). Conclusions: Consumption of crack or cocaine is associated with adverse TB treatment outcomes, particularly loss to follow-up among individuals with active TB. These findings highlight the importance of addressing substance abuse as part of comprehensive TB control strategies.